A note on some applications of semi-open sets - T. M. Nour (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to study the well known notions of semi-closure, semiinterior, semi-frontier and semi-exterior of a set using the concept of semi-open sets. A semi-isolated point of a set is also defined and studied.